Personality Characteristics of Those Who Commit Crimes in a Public Place (by the Example of Mongolia Cities) - Bolor-Erdene Ganmyagmar (Сибирское юридическое обозрение, 2016)
The article handles the problem of studying personalities of those who commit crimes in public places in Mongolia. Most of these crimes are committed by men aged 24-35 year-old males with secondary education, unemployed and alcohol intoxicated. The author distinguishes the following types of persons committing crimes in public places: situational, unstable, malicious and abnormally malicious. The modern Mongolia witnesses these types of crimes as systematic ones. They negatively influence the majority of public being the cause of the citizens’ fear and decreasing the sense of security. The Mongolia Ministry of Justice statistics report proves that crimes in public places are especially evident in Mongolia cities.